2016
DOI: 10.1504/ijise.2016.075809
|View full text |Cite
|
Sign up to set email alerts
|

Condition monitoring of disconnectors in the electric power transmission grid with temperature sensors

Abstract: This paper presents a method that can be used to rank disconnectors in the electric power system, according to the condition of one of the most critical parts, the contacts. The temperature of the contacts can be continuously measured by a new type of infrared sensor. For the case study, 54 sensors were placed on six disconnectors together with reference sensors measuring the ambient temperature. The measured temperature at each contact is then regressed against the ambient temperature and the current through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…However, to measure the resistance of the contacts, the disconnector needs to be out of operation. Hence, an alternative is the measurement of the temperature of the contacts with a new type of infrared sensor [9]. The authors in [9] showed that with additional ambient temperature and current measurement, the coefficient of the current can serve as a measure of the condition of the contacts.…”
Section: Condition Monitoring Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to measure the resistance of the contacts, the disconnector needs to be out of operation. Hence, an alternative is the measurement of the temperature of the contacts with a new type of infrared sensor [9]. The authors in [9] showed that with additional ambient temperature and current measurement, the coefficient of the current can serve as a measure of the condition of the contacts.…”
Section: Condition Monitoring Techniquesmentioning
confidence: 99%
“…Hence, an alternative is the measurement of the temperature of the contacts with a new type of infrared sensor [9]. The authors in [9] showed that with additional ambient temperature and current measurement, the coefficient of the current can serve as a measure of the condition of the contacts. This method becomes cost intensive in large disconnector populations due to the installation of nine temperature sensors, three on each phase of the disconnector and the connection to a wireless communication with is mostly only available in substations.…”
Section: Condition Monitoring Techniquesmentioning
confidence: 99%
“…Then they follow the ratio between the temperature rise of two contacts. Westerlund et al have used IR sensors to follow the condition of disconnector contacts with a model to explain the temperature rise as a function of the current [57].…”
Section: A Current Carryingmentioning
confidence: 99%